The CNDP1 (CTG)5 polymorphism is associated with biopsy-proven diabetic nephropathy, time on hemodialysis, and diabetes duration - Albrecht, Thomas; Braun, Jana D.; Qiu, Jiedong; Peters, Verena; Schmitt, Claus P.; Lammert, Alexander; Köppel, Hannes; Schnülle, Peter; Krämer, Bernhard; Yard, Benito A.; Hauske, Sibylle J. (Journal of diabetes research, 2017)
Considering that the homozygous CNDP1 (CTG)5 genotype affords protection against diabetic nephropathy (DN) in female patients with type 2 diabetes, this study assessed if this association remains gender-specific when applying clinical inclusion criteria (CIC-DN) or biopsy proof (BP-DN). Additionally, it assessed if the prevalence of the protective genotype changes with diabetes duration and time on hemodialysis and if this occurs in association with serum carnosinase (CN-1) activity. Whereas the distribution of the (CTG)5 homozygous genotype in the no-DN and CIC-DN patients was comparable, a lower frequency was found in the BP-DN patients, particularly in females. We observed a significant trend towards high frequencies of the (CTG)5 homozygous genotype with increased time on dialysis. This was also observed for diabetes duration but only reached significance when both (CTG)5 homo- and heterozygous patients were included. CN-1 activity negatively correlated with time on hemodialysis and was lower in (CTG)5 homozygous patients. The latter remained significant in female subjects after gender stratification. We confirm the association between the CNDP1 genotype and DN to be likely gender-specific. Although our data also suggest that (CTG)5 homozygous patients may have a survival advantage on dialysis and in diabetes, this hypothesis needs to be confirmed in a prospective cohort study.